THE EFFECT OF EXCHANGE RATE FLUCTUATIONS ON BALI TOURISM SECTOR - Ignatius Adhi Nugroho; Stephanie Gunawan; Agni Alam Awirya; Putriana Nurman (Jurnal Ekonomi dan Pembangunan, 2025)
Most of the income for Bali tourism comes from foreign tourists expenditure which accounts for more than half of the local tourists. The fact therefore underlines the importance of foreign tourist growth observation due to its significance for Bali economy. This research aims at estimating the change of tourists arrival because of the fluctuation of IDR (depreciation and appreciation) which allegedly thought as one of the underlying factors affecting the number of tourists arrival. This research also aims at analyzing the sensitivity of foreign tourists to the change of traveling cost and at analyzing the tourists destination shift should there be any change of traveling cost and also at analyzing the characteristics of the foreign tourists affected by the exchange rate fluctuations. Event studies showed that exchange rate fluctuation did not affect foreign tourists decision on coming to Bali. This was due to the fact that foreign tourists arrival escalates regardless the exchange rate fluctuation (depreciation and appreciation). Meanwhile, descriptive analyses showed that only minority of foreign tourists were affected by exchange rate fluctuations with analysis characteristic of the country of origin. Moreover, despite the rise of traveling cost to Bali, more than 50% respondents chose to travel to Bali and although there was a change of destination, more than 30% respondents chose other Asian countries as a replacement. It was also revealed that the older the tourists, the less the effect of exchange rate fluctuation on their decision to visit Bali.